Gentrification processes in rururban places: Conceptual assumptions for their study in Colombia. - Nates Cruz, Beatriz (Revista de Antropología y Sociología : Virajes, 2008)
This article is part of a research project on the state of the art of gentrification in rururban places in the municipality of Manizales, Colombia. The text will show the theoretical level of the key concepts of the research: gentrification and rurubanity in correspondence to the local contexts.